The Potential Role of Marine Fungi in Plastic Degradation – A Review - Zeghal, Emna; Vaksmaa, Annika; Vielfaure, Hortense; Boekhout, Teun; Niemann, Helge (Frontiers in Marine Science, 2021)
Plastic debris has been accumulating in the marine realm since the start of plastic mass production in the 1950’s. Due to the adverse effects on ocean life, the fate of plastics in the marine environment is an increasingly important environmental issue. Microbial degradation, in addition to weathering, has been identified as a potentially relevant breakdown route for marine plastic debris. Although many studies have focused on microbial colonization and the potential role of microorganisms in breaking down marine plastic debris, little is known about fungi-plastic interactions. Marine fungi are a generally understudied group of microorganisms but the ability of terrestrial and lacustrine fungal taxa to metabolize recalcitrant compounds, pollutants, and some plastic types (e.g. lignin, solvents, pesticides, polyaromatic hydrocarbons, polyurethane and polyehtylene) indicates that marine fungi could be important degraders of complex organic matter in the marine realm, too. Indeed, recent studies demonstrated that some fungal strains from the ocean, such as Zalerion maritimum have the ability to degrade polyethylene. This mini-review summarizes the available information on plastic-fungi interactions in marine environments. We address (i) the currently known diversity of fungi colonizing marine plastic debris and provide (ii) an overview of methods applied to investigate the role of fungi in plastic degradation, highlighting their advantages and drawbacks. We also highlight (iii) the underestimated role of fungi as plastic degraders in marine habitats.